Enlarged perivascular spaces are linked to freezing of gait in Parkinson's disease - Lin, Fangju; Yang, Baoling; Chen, Ying; Zhao, Wei; Li, Binghan; Jia, Weihua (Frontiers in Neurology, 2022)
Objective: Freezing of gait (FOG) is one of common and disabling gait impairments of Parkinson’s disease (PD). White matter hyperintensity (WMH) and lacunes, as common manifestations of cerebral small vessel diseases (CSVD), have been reported to be associated with gait function in PD patients. However, in the cases with FOG which present with extensive WMH or lacunes, it actually is difficult to distinguish pure PD pathology from vascular origin or combined effects. So far little is known about the correlation between enlarged perivascular space (PVS) and FOG in PD patients. This study aims to explore the role of enlarged PVS in FOG in PD patients. Methods: A total of 95 patients with PD in the absence of obvious WMH and lacunes were included in our study, which were divided into PD-FOG (+) group and PD-FOG (-) group. Demographic and clinical data were investigated. Enlarged PVS in the centrum semiovale (CSO) and basal ganglia (BG) were assessed. The association between enlarged PVS and FOG in patients with PD was analyzed using the multivariate models and the Spearman’s correlation. Results: There were 36 PD patients grouped into PD-FOG (+) (37.9%), with an older age, a longer PD disease duration, and larger numbers of enlarged PVS in CSO and BG compared with PD-FOG (-) group. The highest-severity degree of enlarged PVS burden in CSO was independently associated with FOG in patients with PD (adjusted odds ratio [OR], 3.869; p = 0.022 in multivariable model). The percentages of FOG case increased accompanied by the aggravation of enlarged PVS located in CSO. The grade and count of enlarged PVS in CSO and BG both correlated with FOGQ score in PD patients. Conclusion: Enlarged PVS, particularly in CSO, are associated with FOG in patients with PD, which provides a novel perspective for the mechanisms of FOG in PD.